Study on corrosion behavior of Ni-resist alloys in simulated sea water - Tan, Eileen Mei Ling (2019)
Metals and alloys are widely used in marine industries for their excellent physical properties. However, corrosion may take place when metals or alloys expose to moisture air or corrosive environment and deteriorate their properties. As metals and alloys applied in the marine are exposed to harsh working environment, the rate of corrosion is significantly high. Hence, the selection of metals to be used are vital as corrosion can lead to structural failure and resulting in catastrophic consequences. Among various alloys and metals, Ni-resist alloys, bronze and stainless steels are commonly used in the marine industries due to their strong corrosion resistance. The main objective of this work is to observe the corrosion behaviours of typical electrical submersible pump (ESP) materials, including Ni-resist Type 1, Ni-resist Type D4, Nickel- Aluminium Bronze and Duplex Stainless Steel under different salinity immersions and working temperatures. The metallurgic study of the specimens was conducted using Optical Microscopy to understand their characteristic features. The morphologies of these typical ESP materials after immersion into saline solutions under different conditions were studied using Scanning Electron Microscopy and Energy Dispersive X-ray spectroscopy. The weight loss measurement of specimens after corrosion immersion were carried out to compare how each specimen corrodes under different concentrations of salinity and temperatures. The results show that the rate of corrosion increases with higher temperature and decreases with higher salinity. The results from this experiment can play as a guidance role during material selection at different operation conditions to potentially aid in cost saving arising from replacement of corroded parts and safer environment with minimal risk in corrosion failure.